Tax Research in Accounting: A Look Forward - Hanlon, Michelle (The Accounting Review, 2025)
ABSTRACT To commemorate the 100th anniversary of The Accounting Review, I was asked to provide my forecast of the future of tax research in accounting. In sum, my opinion is that the future is bright and full of opportunities for tax scholars. Governments are altering corporate income tax laws in fundamental ways and questions about how these changes affect investment, investment location, income shifting, corporate capital structure, and financial reporting will be very important aspects to study. New and newly used taxes, such as tariffs and endowment taxes, will allow for novel paths of inquiry and accountants should contribute. The use of AI by tax authorities and taxpayers could alter both tax enforcement and tax planning. The increasing access to administrative data, the use of field experiments and field studies, and employing survey methods to obtain data should expand the settings available to study and improve identification.